Forced convection and the coffee cup - Ferreira, João Paulo M. (2025)
Different heat transfer mechanisms are often presented to students only in an expositive way, lacking experimental demonstrations. Using the common situation of the cooling of a coffee cup, a series of practical activities are here proposed that require simple, accessible, and inexpensive equipment. Emphasis is placed on the effect of forced convection, vs free convection. The implications of these in relation to other heat transfer mechanisms, specifically radiation and evaporation, are studied. Quantitative analyses are possible, enabling to estimate values of heat transfer coefficients. These are compared with predictive correlations of dimensionless numbers, arriving at very good agreements.